2021
DOI: 10.1186/s10020-021-00330-2
|View full text |Cite
|
Sign up to set email alerts
|

CircMTO1 inhibits ox-LDL-stimulated vascular smooth muscle cell proliferation and migration via regulating the miR-182-5p/RASA1 axis

Abstract: Background Circular RNAs (circRNAs) play critical roles in the development of atherosclerosis (AS). This study investigated the role of circMTO1 in the progression of AS. Methods Serum samples from AS patients and healthy volunteers and vascular smooth muscle cells (VSMCs) were used as the study materials. The expressions of circMTO1 and miR-182-5p were measured by RT-qPCR. The effects of circMTO1, miR-182-5p, and RASA1 on VSMC proliferation and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“… 3 It is widely reported that circRNA plays an important role in cell and tissue proliferation. 4 , 5 For example, circGCN1L1 promotes cell proliferation and apoptosis by targeting miR-330-3p and TNF-α. 6 CircRNAs play important roles in CRSwNP occurrence.…”
Section: Introductionmentioning
confidence: 99%
“… 3 It is widely reported that circRNA plays an important role in cell and tissue proliferation. 4 , 5 For example, circGCN1L1 promotes cell proliferation and apoptosis by targeting miR-330-3p and TNF-α. 6 CircRNAs play important roles in CRSwNP occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…However, lower levels of circMTO1 in the serum of humans with atherosclerosis coincided with augmentation of miR-182-5p, increased proliferation, and reduced apoptosis in an in vitro analysis of ox-LDL-stimulated VSMCs. Overexpression of circMTO1 led to less inhibition of miR-182-5p and subsequently greater activation of the RASA1 gene, reduced proliferation, and increased apoptosis of VSMCs [ 57 ]. Similarly, while lower levels of circ_0065149 were observed in a model of ox-LDL human umbilical vein ECs in vitro, overexpression was associated with miR-330-5p sponging and associated effects of increased cell viability, proliferation, and migration, but reduced apoptosis and inflammation [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sponging the same miRNA by different circRNAs also had contradictory effects on cell proliferation, apoptosis, and inflammation. For example, miR-182-5p was demonstrated to be affected downstream of four different circRNA molecules: circ_USP36, circMTO1, hsa_circ_0004831, and Circ_0050486 [ 42 , 57 , 77 , 142 ]. While sponging of miR-182-5p by circ_USP36 led to increased activity of the KLF5 gene, which induced VSMC proliferation and metastasis, inhibition of miR-182-5p via overexpression of circMTO1 and subsequent RASA1 gene activation had the opposite effects of decreased VSMC proliferation and decreased apoptosis ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, circMTO1 represses the proliferative and migrative abilities of VSMCs stimulated by Ox-LDL via the miR-182-5p/RASA1 axis. 16 miR-663 has been elucidated to manipulate the phenotype change of human VSMCs and vascular neointimal formation and play an active role in VSMCs proliferation. 17 In addition, miR-663 plays an indispensable role in endothelial dysfunction, AS, and inflammatory response.…”
Section: Introductionmentioning
confidence: 99%